Implementasi Kurikulum K13 Dalam Manajemen Berbasis Sekolah di SMA Kristen Alfa Omega Tumpaan - Tambaritji, Desy; Siang, Jhoni Lagun; Kambey, Ellen S. (Jurnal Ilmiah Wahana Pendidikan, 2024)
The aimed of this research was to analyze: 1). The implementation of the K13 Curriculum in school-based management at Alfa Omega Tumpaan Christian High School, 2). The supporting factors for the implementation of the K13 curriculum in school-based management at Alfa Omega Tumpaan Christian High School, 3). The inhibiting factors for the Implementation of the K13 Curriculum in School-Based Management Schools at Alfa Omega Tumpaan Christian High School, 4). The efforts have been made to overcome inhibiting factors in increasing the success of the implementation of the K 13 curriculum in school-based management at Alfa Omega Tumpaan Christian High School. The method used in this research was qualitative descriptive. The data was collected by using observation, interview and documentation study. The results of the research that the implementation of the K13 curriculum in school was not optimal, because the government and the foundation do not pay enough attention to the school, especially in sending teachers, facilities and infrastructure, and improving the quality of teachers through education and training, and seminar so that the interest of the society toward the school was low